Keterbatasan penelitian peran penduduk kampung adat ciptagelar dalam upaya menjaga kelestarian hutan: Metode bibliografi - Ghaida Nurin Athifah; Hertien Koosbandiah Surtikanti (Social, Ecology, Economy for Sustainable Development Goals Journal, 2024)
The bibliography is a method that can be used to see and analyze topic trends in research. One topic that has yet to be widely researched is the forest area in the Ciptagelar Traditional Village. This topic relates to how the people of Ciptagelar Traditional Village protect and preserve their forest area. Therefore, this research article aims to analyze the frequency of scientific publications indexed by Google Scholar regarding the forest area of Ciptagelar Traditional Village. The method used in this research is bibliographic analysis using Co-word. The database used as material for this research is a database of scientific publications indexed by Google Scholar, totaling 449 publications with several search keywords. This research shows an increase in publications in the last 5 years. Apart from that, groups with a low keyword network level are forest with development and forest with study.